Histomorphological Features of Atypical Small Acinar Proliferations (ASAP) That Favor Malignancy - Ayşe Gökçen Sade; Şükran Sarıkaya; Nagehan Özdemir Barışık; Cem Cahit Barışık; Sibel Şensu (Southern Clinics of Istanbul Eurasia, 2021)
INTRODUCTION[|]Cases diagnosed as atypical small acinar proliferation (ASAP) in prostate transrectal ultrasound (TRUS) biopsies typically require rebiopsies, which are invasiveand associated with increased risk of complications. Therefore, reduction in the rates of ASAP diagnoses during initial biopsy interpretation will decrease the need forrebiopsy and limit the burden of new diagnostic procedures. The current study aimed to investigate patient demographics, serum PSA levels, and histopathological features of cases identified as 'ASAP' during initial prostate biopsies and as 'benign' or 'malignant' in the rebiopsies.[¤]METHODS[|]This retrospective study included 187 cases and 257 core biopsies with a diagnosis of ASAP. Initial age and serum PSA levels were recorded, and the cores were analyzed histopathologically. The presence of nuclear enlargement, prominence of nucleoli, cytoplasmic amphophilia, luminal acellular secretions, cristalloids, infiltrative growth pattern, atrophy, inflammation, and number of the suspicious acini were recorded. Adenocarcinomas were identified using the Gleason score.[¤]RESULTS[|]The mean age and serum PSA levels were significantly higher in the intermediate-high grade malignant group compared to the other groups, while nuclear enlargement (>2 times) and prominent nucleoli were more frequently observed in the malignant group compared to the benign group. Amphophilic cytoplasm and luminal acellular amorphous eosinophilic secretions were more frequently observed in malignant groups, while the benign group exhibited higher rates of inflammation.[¤]DISCUSSION AND CONCLUSION[|]The findings of the current study showed enlargement of the nuclei (≥2 times), nucleolar prominence, amphophilic cytoplasm, luminal amorphous acellular secretion, and absence of inflammation were associated with malignancy. Moreover, higher mean age and serum PSA level were related with intermediate-high grade malignancy, and consideration of these factors during evaluation of initial TRUS biopsies may decrease the prevalence of ASAP diagnoses and prevent unnecessary interventions.[¤]